2020
DOI: 10.1177/1559325820904858
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antihypercholesterolemic Activities of Pulicaria gnaphalodes

Abstract: Multidrug resistance has increased globally in the communities. Bacterial infections associated with health care have weakened the existing antimicrobial therapy and demand the search for alternative therapies. In the present investigation, the medicinal plant Pulicaria gnaphalodes from Quetta, Pakistan, has been screened for antimicrobial potential. In vitro antimicrobial efficacy of P gnaphalodes extracts (methanol and ethanol) was quantitatively evaluated on the basis of zone of inhibition against different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…The Gram negative bacteria also offer more resistance to antibacterial agents as compared to the Gram positive bacterial strains such as S. typhi is one that cause severe food borne illness known as typhoid fever and is treated with a set of antibiotics instead of single antibiotic. 37 , 38 The results of the study were compared with the ciprofloxacin taken as standard antibacterial agent, it showed strong growth inhibition of P. aeruginosa with 25.5 ± 1.21 mm ZOI followed by 20.2 ± 1.10 mm ZOI against K. pneumonia , however some results were missed due to COVID-19 epidemic lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…The Gram negative bacteria also offer more resistance to antibacterial agents as compared to the Gram positive bacterial strains such as S. typhi is one that cause severe food borne illness known as typhoid fever and is treated with a set of antibiotics instead of single antibiotic. 37 , 38 The results of the study were compared with the ciprofloxacin taken as standard antibacterial agent, it showed strong growth inhibition of P. aeruginosa with 25.5 ± 1.21 mm ZOI followed by 20.2 ± 1.10 mm ZOI against K. pneumonia , however some results were missed due to COVID-19 epidemic lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample’s activity was checked by measuring the zones of growth inhibition developed in millimeters with the help of a graduated scale. 34 …”
Section: Methodsmentioning
confidence: 99%
“…The composite scaffolds can recognize favorable mechanical strength hydrophilicity and appropriate degradation process. A natural polysaccharides chitosan is utilized in various clinical applications, involving wound healing, nerve regeneration, and bone repairing (Jiankang et al, 2009;Naqvi et. al., 2020).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%